Nematode parasites of vertebrates : their development and transmission - Anderson, Roy C. 1926- (CABI, 2000)
The first edition of this book was published in 1992 (see Helminthological Abstracts (1993) 62, abstract 1457). This new enlarged edition includes additional relevant information from some 450 articles published between 1989 and 1998 (with a few from 1999), and some articles overlooked or unavailable for the first edition. The number of species covered has been increased by 34 (total now 595). As before, the book is in 2 parts, the Secernentea and Adenophorea, which are now regarded as classes rather than subclasses. The Secernentea covers the orders Rhabditida, Strongylida, Oxyurida, Ascaridida and Spirurida (suborders Camallanina and Spirurina), and the Adenophorea covers the order Enoplida, with the Dioctophymina and Trichinellina now treated as separate suborders. The aim of the book remains "to summarize and synthesize knowledge of the basic features of the development and transmission of parasitic nematodes of vertebrates, and to place this information in the context of the modern classification as found in the CIH Keys to the Nematode Parasites of Vertebrates" [but see the 2 departures from these keys as noted above]. Nematode parasites of humans, domestic animals and wildlife (including fish) are covered. Each chapter or part begins with an overview of the mode of feeding, habitat and life cycles of the group. This is followed by descriptions and illustrations of larval stages of named specific examples. The number of illustrations has been increased from 33 to 43. Comprehensive bibliographies appear at the end of the sections on each order or suborder.